2019
DOI: 10.26504/qec2019spr_sa_bergin
|View full text |Cite
|
Sign up to set email alerts
|

Ireland and Brexit: modelling the impact of deal and no-deal scenarios

Abstract: This Article attempts to quantify the macroeconomic impact of Brexit on the Irish economy. Given both the political and economic uncertainty, we consider a range of alternative scenarios. We focus on the most well understood channels through which Brexit will affect Ireland, namely though lower trade, incorporating the impact of tariff and non-tariff measures, and the potentially positive impact of FDI diversion to Ireland. Our approach, and the main contribution of this paper, is to build up estimates of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…al, 2019). At the same time, existing evidence indicates that RoI will be hit relatively hard compared to other EU countries given the open nature of the economy and its close economic relationship with the UK (see, for example, Dhingra et al, 2016;Kierzenkowski et al, 2016;Vandenbussche et al, 2019;Bergin et al, 2019). At a regional level, a recent assessment (Hantzsche and Young, 2019) of the potential impact of a customs union between the UK and EU, found that NI is one of the regions likely to be adversely affected by Brexit (8 th most negative impact out of 40 NUTS 2 regions considered.…”
Section: Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…al, 2019). At the same time, existing evidence indicates that RoI will be hit relatively hard compared to other EU countries given the open nature of the economy and its close economic relationship with the UK (see, for example, Dhingra et al, 2016;Kierzenkowski et al, 2016;Vandenbussche et al, 2019;Bergin et al, 2019). At a regional level, a recent assessment (Hantzsche and Young, 2019) of the potential impact of a customs union between the UK and EU, found that NI is one of the regions likely to be adversely affected by Brexit (8 th most negative impact out of 40 NUTS 2 regions considered.…”
Section: Existing Literaturementioning
confidence: 99%
“…However, factors such as reduced access to the EU single market and uncertainty about the UK's future relationship with the EU mean it is likely that inward FDI to the GB and NI will be lower in the long-run (see, for example, Ebell and Warren, 2016;Dhingra et al 2017). 11 For the RoI, given that it is already an attractive destination for FDI, Brexit could lead to an opportunity for firms to relocate investment in order to remain within the EU with full access to the EU single market or some FDI that otherwise would have gone to the UK (in the absence of Brexit) may be diverted to the RoI (Lawless and Morgenroth, 2016;Bergin et al 2019).…”
Section: The Importance Of the Multinational Sectormentioning
confidence: 99%
“…The Irish and the United Kingdom economies are deeply integrated across several dimensions including trade and the labour market (Arriola et al, 2018). Production processes in many industries are increasingly fragmented across national borders and a common labour market was established between the two countries even before EU membership (Bergin et al, 2019) As such, Brexit has a large effect on the Irish economy, more than other EU member state. Even with a UK-EU FTA, Irish GDP would decline 2.0% in the medium term, where much of the decline is due to divergence in regulations.…”
Section: The Effects Of Leaving the Single Market On Individual Eu Mementioning
confidence: 99%
“…The UK is deeply integrated with the EU and its decision to exit from this trading block has no parallel in modern history 26. Almost one-half of the UK’s food is imported: 30% comes from the EU, and another 11% comes from non-EU countries under the terms of trade deals negotiated by the EU.…”
Section: Introductionmentioning
confidence: 99%